EXPERIMENTAL STUDY OF SAMPLES MANUFACTURED FROM CRUSHED POLYMER WASTE ON A 3D PRINTER WITH A SCREW EXTRUDER - POLISHCHUK, ANDRII; SKYBA, MYKOLA (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The article conducts an experimental study of samples made from crushed polymer waste on a 3D printer with a screw extruder. General information about the experimental study is given. An analysis of literary sources on the study of mechanical properties of products manufactured by FDM technology on 3D printers was carried out. Two 3D printers were chosen for the production of experimental prototypes, one of which prints with filament, the other with granules or crushed polymer waste. The equipment for determining the accuracy of printed samples has been selected. The measuring part of the tearing machine for taking tensile diagrams of polymer samples has been improved. A strain gauge for force measurement and an optical encoder for displacement measurement are installed in it. A digital electronic system for data collection from sensors based on the Arduino Uno microcontroller was developed. Software for experimental data processing was created. The general view of the experimental setup is given. It is proposed to use uniaxial tension to evaluate the mechanical characteristics of the test samples printed on a 3D printer. Current international standards for tensile testing of plastics are described. To determine the mechanical tensile characteristics, samples in the shape of a blade were made from polymer materials ABS and TPU. The parameters for printing test samples made from these materials are set. With the use of the developed installation, the failure diagrams of samples (blades) made of crushed polymer waste and filament of ABS and TPU plastics with different amounts of internal filling were obtained. In the form of tables, the values of the mechanical characteristics of the samples produced by the 3D printing method from ABS and TPU polymers with different internal filling obtained during the uniaxial tensile test are presented. A photo of the places of breakage of ABS plastic blades, taken using a digital camera, is given. An analysis of the structure of the samples was carried out on them. Experimental test samples were made using two 3D printers to determine the accuracy of 3D printing. Measurements were made in different planes of the test cube using a digital electronic caliper. The obtained results were compared with the created model. Ways to improve print accuracy are described.